From Prodrug to Multimatrix: Recent Advancement of Colon Specific Drug Delivery System - Saha, Sabuj Kumar; Hasan, A.H.M. Nazmul; Anjum, Ramisa; Rimun, Shariun Nahar; Rahman, Nujhat Zayma; Akanda, Md. Khokon Miah; Buhiyan, Mohiuddin Ahmed; Islam, SM Ashraful (Sciences of Pharmacy, 2024)
Prevalence of colonic diseases such as inflammatory bowel disease, colorectal cancer, angiodysplasia, salmonellosis, etc, are increasing daily and are reducing the quality of life of the patients. These diseases can be difficult to treat due to their ability to alter the normal environment of the colon such as the pH, microbiota, enzymes, and more. Anatomy and physiology of the colon also pose difficulty in case of targeted drug administration. Additionally, there are variations in how each colonic disease influences the colon, making it essential to design a Colon-Specific-Drug-Delivery System (CSDDS) that would ensure proper targeting and delivery of the drugs. To reduce systemic side effects and achieve desired therapeutic effects, the dosage form should be designed in such a way that allows for direct and precise targeting of drugs into the colon, while also preventing premature gastrointestinal drug release. In this review, we discuss the conventional (for example, prodrug, CODES, pulsatile drug delivery) and novel (OPTICORE, Phloral, MMX technology, 3D bicompartmental device) approaches aimed at ensuring drug release and absorption within the colon, as well as examine the factors that affect drug delivery targeted at the colon. Despite considerable progress, significant challenges and gaps remain, including the need for a deeper understanding of colonic environmental variability, the development of advanced biocompatible materials, and the implementation of personalized treatment strategies are highly required.